The Relationship of Open-mindedness to Social Intelligence for Fourth Graders in the Department of Qur’anic Sciences and Islamic Education - Ibrahim, Basher Khaleel (Journal of Tikrit University for Humanities, 2024)
The aim of the current research is to find the relationship between mental openness and social intelligence among students of the Department of Qur’anic Sciences and Islamic Education at Al-Turbah Basic College. The research sample consisted of 40 male and female students in the fourth year in the Department of Qur’anic Sciences and Islamic Education. The researcher adopted two tools, the first a measure of social intelligence prepared by Al-Taie and Al-Hasso (2009), the second a measure of mental openness prepared by Abdel Latif and Mahmoud (2019), and another measure prepared by Al-Sumaidaie and Al-Obaidi. (2019). The researcher applied the two tools after ensuring their validity and reliability, and then analyzed the results statistically using a number of statistical methods. At the end of the research, the researcher reached a number of conclusions, recommendations and proposals.